PENGARUH LABEL HALAL, CITRA MEREK, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK WARDAH (Studi Kasus Pada Konsumen Produk Wardah di Kota Tangerang) - Ayu Oktavia, Dian (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2025)
This study aims to examine the effect of the halal label, brand image and product quality on the purchase decision of Wardah products for consumers of Wardah products in Tangerang City. The population in this study are users of Wardah products in Tangerang City. The sample used was 154 respondents using Wardah products. In this study, the sampling technique used was Non-Probability Sampling and the type of sampling design in this study was purposive sampling. The data collection method in this study was to use a questionnaire (questionnaire). In this study, the data analysis method used SPSS software or Statistical Package for the Social Sciences Method Version 2.5. The results of this study found that the halal label, brand image and product quality had a positive and significant effect on the decision to purchase Wardah halal cosmetic products.